Trypanosoma brucei gambiense Group 2: The Unusual Suspect. Issue 12 (December 2019) - Jamonneau, Vincent; Truc, Philippe; Grébaut, Pascal; Herder, Stéphane; Ravel, Sophie; Solano, Philippe; De Meeus, Thierry
Abstract : Trypanosoma brucei causes human African trypanosomiasis (HAT). Three subspecies were described: T. b. gambiense ( Tbg ) and T. b. rhodesiense ( Tbr ) in humans, and T. b. brucei ( Tbb ) in animals. Molecular markers subdivided Tbg into two groups: Tbg 1 and Tbg 2, of which the latter is different from Tbg 1 and Tbr (absence of the SRA gene), but indistinguishable from Tbb . Tbg 2 is considered to be a zoonotic form of HAT in West Africa. Tbg 2 was found mainly in Côte d'Ivoire between 1978 and 1992, but the latest description was made in Ghana in 2013. New molecular tools would be welcome to characterize such infections and determine their origins (resistance to human serum or patient immunodeficiency) in the current context of HAT elimination. Highlights: Tbg 2 was defined as all human-infective T. brucei trypanosomes from West and Central Africa that do not fit into the category Tbg 1. Tbg 2 is genetically heterogeneous, and differs from Tbg 1 when using various molecular markers. Tbg 2 is also genetically different from Tbr, with a consistent lack of the serum-resistance-associated gene in those strains that were tested. Tbg 2, Tbb, and Tbr are highly diverse lineages that remain to be investigated more thoroughly. Tbg 2 was found mainly in Côte d'Ivoire between 1978 and 1992, but the latest descriptions of Tbg 2 were made in Ghana in 2003 and 2013. No other record could be found between 1992 and 2003. Tbg 2 represents a zoonotic form of HAT. Human infectivity probably arose multiple times and so could do so again. In the elimination context, it is crucial to detect such infections and determine their origins (resistance to human serum or patient immunodeficiency).